Implications of E-Commerce and Fintech on Changes in Consumption Patterns in Generation Z Consumers Case Study: Shopee and Brimo Application Users in Bojonegoro Regency (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to find out the influence of the implications of E-Commerce and Fintech on changes in consumption patterns of generation z. In this study, a quantitative approach was used with the data collection used to distribute questionnaires to users of the Shopee and BRImo applications in Bojonegoro Regency with techniques Purposive sampling, a sample that is taken based on certain criteria or characteristics chosen by the researcher. The results of the study show that E-commerce has an effect on changes in the consumption pattern of generation z in Bojonegoro Regency. Meanwhile, Fintech has no effect on changes in the consumption pattern of generation z in Bojonegoro Regency.